Accuracy of cone-beam computed tomography, dental magnetic resonance imaging, and intraoral radiography for detecting peri-implant bone defects at single zirconia implants: an in vitro study - Hilgenfeld, Tim; Jürchott, Alexander; Deisenhofer, Ulrich; Krisam, Johannes; Rammelsberg, Peter; Heiland, Sabine; Bendszus, Martin; Schwindling, Franz Sebastian (Clinical oral implants research, 2018)
Objectives To evaluate the diagnostic value of cone-beam computed tomography (CBCT), intraoral radiography (IR), and dental magnetic resonance imaging (dMRI) for detecting and classifying peri-implant bone defects at zirconia implants. Materials and Methods Forty-eight zirconia implants were inserted in bovine ribs, 24 of which had standardized defects (1-wall, 2-wall, 3-wall, 4-wall) in two sizes (1 and 3 mm). CBCT, IR, and dMRI were performed and analyzed twice by four readers unaware of the nature of the defects. Cohen's and Fleiss' kappa (κ), sensitivity, and specificity were calculated for the presence/absence of bone defects, defect size, and defect type. Cochran's Q-test with post hoc McNemar was used to test for statistical differences. Results A high intra- and inter-reader reliability (κ range: 0.832-1) and sensitivity/specificity (IR: 0.97/0.96; CBCT: 0.99/1; dMRI: 1/0.99) for bone defect detection were observed for all three imaging methods. For defect type classification, intra- (κ range: 0.505-0.778) and inter-reader (κ: 0.411) reliability of IR were lower compared to CBCT (κ range intrareader: 0.667-0.889; κ inter-reader: 0.629) and dMRI (κ range intrareader: 0.61-0.832; κ inter-reader: 0.712). The sensitivity for correct defect type classification was not significantly different for CBCT (0.81) and dMRI (0.83; p = 1), but was significantly lower for IR (0.68; vs. CBCT p = 0.003; vs. dMRI p = 0.004). The sensitivity advantage of CBCT and dMRI for defect classification was smaller for 1-mm defects (CBCT/dMRI/IR: 0.68/0.72/0.63, no significant difference) than for 3-mm defects (CBCT/dMRI/IR: 0.95/0.94/0.74; CBCT vs. IR p = 0.0001; dMRI vs. IR p = 0.003). Conclusion Within the limitations of an in vitro study, IR can be recommended as the initial imaging method for evaluating peri-implant bone defects at zirconia implants. CBCT provides higher diagnostic accuracy of defect classification at the expense of higher cost and radiation dose. Dental MRI may be a promising imaging method for evaluating peri-implant bone defects at zirconia implants in the future.